Impact of Overclaims, Negative E-Wom, and Dissatisfaction on Switching Intention: The Moderating Role of Alternative Attractiveness - Cahyo, Septian Dwi; Dewi, Adhisty Kartika; Kuwatno (Jurnal Ekonomi dan Bisnis, 2025)
This study discusses switching intention in the rapidly growing Indonesian local skincare industry, which is marked by excessive promotional claims (overclaims), negative online reviews (negative e-WOM), and consumer dissatisfaction. The objective of this research is to analyze the influence of these negative factors on switching intention, with alternative attractiveness serving as a moderating variable. The study employed a quantitative approach using an online survey involving 151 users of local skincare products selected through purposive sampling. The data were analyzed using WarpPLS 8.0. Overclaims, negative e-WOM, and dissatisfaction have a significant positive effect on switching intention. Alternative attractiveness strengthens the influence of negative e-WOM and dissatisfaction, but weakens the effect of overclaims. These findings highlight the importance of honest product claims, effective online reputation management, and consumer satisfaction in minimizing the risk of brand switching in a market filled with attractive alternatives. This study makes a theoretical contribution by demonstrating the role of alternative attractiveness, a factor that has rarely been examined in the local skincare industry